ISTIHSAN; ANALISIS HISTORIS PEMIKIRAN IMAM AS-SYAFI’I - Jainuddin H. Tajudin (Fakultas Syariah IAI Muhammadiyah Bima, 2017)
Imam Syafi’I rejected the concept of Istihsan based on his reason, if someone uses the Ihtihsan as his reason, so he has made a new syare’at. As known, Imam Syafi’I committed to use Al-qur’an, As-Sunnah, Ijma’ and Qiyas as the mind of his construction thinking. It was not born suddenly, but influenced by other elements. Imam Syafi’I is the great Muslim Figure known by multidiscipline knowladge; he developed the Hizza’s model in his thinking which influenced by shades of science at Madinah and Iraq. To know deeply, this research uses the historical-approach, it purposes to know more easy his thinking about Istihsan and how it was born. Besides, Imam Syafi’I was not rejected totally the concept of istihsan, but there are some reasons to receive it. Refer to it, Imam Syafi’I rejected the concept of istihsan because it was assumed using extra logically in Istimbat.